Marketing System of Fresh Friut and Vegetable: The Role of Modern and Wholesale Market in Jakarta and the Vicinity - Napitupulu, Togar A. (Binus Business Review, 2010)
Marketing system of fresh fruits and vegetable in the context of the rapidly growing dynamic markets in Jakarta and the vicinity was studied. Unstructured interviews and observations of key persons, and panels were conducted, primarily in three main wholesale markets in Jakarta and the vicinity and some supermarkets. It was found that the availability of management services and associated facilities are not yet fully compatible with modern markets. Their role, therefore, in catering to the supermarkets is limited, in particular for vegetables due to requirements on quality and delivery schedules. In general, supermarkets procure their supply directly from production centers through special/dedicated suppliers, which currently amounts to about 1% to 5% of total production from production centers. If policy and conducive economic incentive are available, wholesale markets are not only domain of public investment anymore, but also private investments alike. The newly established wholesale markets show that they now have a higher rate of utilization than in the years before. It is therefore for the local government and the central government to furthers devise conducive policy and regulatory measures, and for the private to take this opportunity in terms of investment in developing the economy of the region.Â